Densidad de siembra del Zea mays Marginal 28 y su efecto en las características agronómicas y rendimiento del forraje bajo sistema de riego con aspersión en Zungarococha - Loreto. 2022 - Angulo Flores, Claider Aldo (2023)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Cattle Project on the Zungarococha Farm, entitled "SEEDING DENSITY OF MARGINAL Zea mays 28 AND ITS EFFECT ON AGRONOMIC CHARACTERISTICS AND FORAGE YIELD UNDER IRRIGATION SYSTEM WITH ASPERSION IN ZUNGAROCOCHA – LORETO. 2022”. The evaluations were carried out 45 days after the beginning of the research work, with plots of 5 m x 5 m (25 m2) and an experimental area of 391 m2. With a Randomized Complete Block Design (D.B.C.A), with three treatments and four repetitions, the treatments under study were: T1 (2 seeds/ corn blow), T2 (4 seeds/ corn blow) and T3 (6 seeds/ corn blow), where a yield of plant height (m) of 1.75 m., yield of green matter (kg/m2) of 4.27 kg/m2., yield of dry matter (kg/m2) of 0.90 kg was achieved. /m2., the Number of leaves/plant of 17.25., the Ratio leaf/stem (kg) of 0.75 kg. And a yield of green matter kg/ha of 42650 kg/ha. In this sense, it was shown that at least one planting density influenced the agronomic characteristics and forage yield of tropical Zea mays MARGINAL 28 under an irrigation system by aspersion.